E-portf olio: from professional training technology to self-promotion one at the labour market - Petrenko, Larysa (Professional Pedagogics, 2018)
Economic and high technologies development outline the issue of in-time offers for educational services providing. E-portfolio technology is widely spread in many countries. Their design and use for a person’s own development led to the development of a separate infrastructure. E-portfolio’s synergy helps to create a virtual community as a single electronic educational space. Everyone can use it despite of age and/or social status. Active development of information technology has led to the transformation of the E-portfolio as a technology online professional training and a web-based portfolio to picture the educational progress or professionalism growth. Created E-portfolios and their share in the virtual community demonstrates intellectual ability and logic thinking, reflects the range of students’, trainees’ and training participants’ activities, methods, confirms their ability to perform a particular job. The article shows an E-portfolio’s efficiency as a ICT competence development for VET school Heads. The possibility to use E-portfolios during the interview (interviews) with an employer as a presentation of own competence, experience and achievements in the responses to questions, as well as reflection of personal skills is represented. The scientific novelty of study results is that in national professional pedagogic an E-portfolio is firstly considered as an employment concept, life long career development, the unique modern electronic technology, the way of self-presentation, self-promotion in the labor market that meets key global trends in recruitment. The experience of foreign universities in E-portfolio use as a professional training technology and a person’s specific achievements throughout his/her life is generalized.